2008
DOI: 10.1016/j.ijrobp.2007.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Intratumor Distribution of 18F-Fluoromisonidazole in Head and Neck Cancer

Abstract: Purpose-Hypoxia is one of the main causes of the failure to achieve local control using radiotherapy. This is due to the increased radioresistance of hypoxic cells. 18 F-fluoromisonidazole ( 18 F-FMISO) positron emission tomography (PET) is a noninvasive imaging technique that can assist in the identification of intratumor regions of hypoxia. The aim of this study was to evaluate the reproducibility of 18 F-FMISO intratumor distribution using two pretreatment PET scans.Methods and Materials-We enrolled 20 head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
130
5
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(147 citation statements)
references
References 28 publications
11
130
5
1
Order By: Relevance
“…These results suggest that vascular remodelling might be responsible for the slower frequency of cycling hypoxia. Recent 18 Fmisonidazole (a hypoxia marker drug) positron-emission tomography (PET) studies in human patients with head and neck cancer have verified that large regions of tumours can experience the slower frequency cycling hypoxia 98 . In these studies, serial PET studies scheduled 3 days apart showed that hypoxic tumour zones moved or changed in size between sequential studies.…”
Section: Mechanisms Underlying Cycling Hypoxia and Implicationsmentioning
confidence: 99%
“…These results suggest that vascular remodelling might be responsible for the slower frequency of cycling hypoxia. Recent 18 Fmisonidazole (a hypoxia marker drug) positron-emission tomography (PET) studies in human patients with head and neck cancer have verified that large regions of tumours can experience the slower frequency cycling hypoxia 98 . In these studies, serial PET studies scheduled 3 days apart showed that hypoxic tumour zones moved or changed in size between sequential studies.…”
Section: Mechanisms Underlying Cycling Hypoxia and Implicationsmentioning
confidence: 99%
“…A particular concern is the time delay between scans and initiation of treatment. Nehmeh and colleagues [30] examined the regional spatial repeatability of FMISO hypoxia scans by performing two scans 3 days apart, followed by a voxel-by-voxel comparison of the two scans. Interestingly, although many patients showed reasonable scan-to-scan correlation nearly half of the patients were characterized by a poor geographical match between the two scans, which may severely, reduce the efficacy of hypoxia-targeting intensity modulated radiotherapy [31].…”
Section: Discussionmentioning
confidence: 99%
“…High spatial resolution of the intensity modulated beams is needed to provide the irregular dose distributions required. It may also be relevant to evaluate the temporal evolution of image parameters during the course of treatment [9,21], as this may have an impact on the dose prescription map. The situation is further complicated by the considerable geometrical uncertainties taking place during RT (bladder/tumor motion) for the present patient group [22].…”
Section: Discussionmentioning
confidence: 99%